2006
DOI: 10.1096/fj.05-3815hyp
|View full text |Cite
|
Sign up to set email alerts
|

Can specific biological signals be digitized?

Abstract: At the request of the United States Defense Advanced Research Projects Agency, we attempted to replicate the data of Professor Jacques Benveniste that digital signals recorded on a computer disc produce specific biological effects. The hypothesis was that a digitized thrombin inhibitor signal would inhibit the fibrinogen-thrombin coagulation pathway. Because of the controversies associated with previous research of Prof. Benveniste, we developed a system for the management of social controversy in science that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 12 publications
1
31
0
1
Order By: Relevance
“…Most of these issues emerged when the OAM held the first NIH conference on definitions and epistemology [9]. These were quickly followed by NIH technology assessment conferences on meditation and mind-body practices [17], acupuncture [18], the role of placebo in medicine and research [19], and the use of social conflict management for assuring completion of studies in controversial areas like cancer [20] and homeopathy [21]. Some of these issues were subsequently taken up both inside and outside the alternative medicine fields.…”
Section: What Is In a Name? Perhaps Everythingmentioning
confidence: 99%
“…Most of these issues emerged when the OAM held the first NIH conference on definitions and epistemology [9]. These were quickly followed by NIH technology assessment conferences on meditation and mind-body practices [17], acupuncture [18], the role of placebo in medicine and research [19], and the use of social conflict management for assuring completion of studies in controversial areas like cancer [20] and homeopathy [21]. Some of these issues were subsequently taken up both inside and outside the alternative medicine fields.…”
Section: What Is In a Name? Perhaps Everythingmentioning
confidence: 99%
“…However, the contention that digital signals recorded on a computer disk produce specific biological signals was not confirmed in a replication trial. 41 Admittedly, there still remains some uncertainty about details of water structure, and further in-depth studies are necessary to provide deeper insight into the nature of this substance, which may further our understanding of the philosophy and science of homeopathic potentization.…”
Section: Does Research On Homeopathy Need Special Considerations?mentioning
confidence: 99%
“…The results of this expertise have been described in an article in 2006 (Jonas et al 2006). The authors concluded that results supporting ''digital biology'' were obtained when members of Benveniste's team were present, but they were unable to reproduce these results in their absence.…”
Section: A Need For a Theoretical Frameworkmentioning
confidence: 99%